Gender differences in sagittal standing alignment before pubertal peak growth: the importance of subclassification and implications for spinopelvic loading. Issue 6 (24th September 2013) - Dolphens, Mieke; Cagnie, Barbara; Vleeming, Andry; Vanderstraeten, Guy; Danneels, Lieven
Abstract: The aim of this study was to analyze gender differences in sagittal standing alignment at pre‐peak height velocity age thereby applying a scientifically sound and practically oriented classification scheme for overall standing balance. The study population consisted of healthy boys ( n = 639) and girls ( n = 557) before pubertal peak growth. During subjects' habitual standing, sagittal plane measures of the spine, pelvis and lower limbs were collected using a clinical screening protocol. With each subject classified as one of three postural types (neutral, sway‐back, or leaning‐forward), differences in sagittal plane alignment were analyzed between sexes. The results revealed clear differences between genders in each of the postural types. Within the neutral and sway‐back postural subgroups, boys presented more forward inclination of the trunk, more thoracic kyphosis and more pelvis backtilt compared with girls. Within the leaning‐forward category, girls displayed more forward trunk lean, less thoracic kyphosis and more pelvic anteversion. A state of lumbar segmental hyperextension appeared to exist in female leaning‐forward subjects. Our results reveal for the first time that sagittal standing alignment is different between prepubescent boys and girls when subjects are appropriately subclassified, and conversely represent a 'wash‐out effect' when pooled. When the classification system is applied, gender‐specificity in gravity line position is suggested, implying gender‐related differences in lever arms and thus load. Present findings may add to our understanding of gender‐specific biomechanical challenges posed by habitual posture, and may shed new light on sagittal standing alignment as a possible contributory factor in developmental spinal‐pelvic disorders.